RELACIONAMENTO INTERPESSOAL E SATISFAÇÃO PROFISSIONAL DA EQUIPE DE ENFERMAGEM NA REDE HOSPITALAR PÚBLICA - OLIVEIRA, Carlos Amaral de Sousa (2017)
Nursing work has as a characteristic the development of its assistance activities centered on teamwork, with communication being the main instrument for interpersonal relationships. Errors in communication lead to conflicts and affect caring. This study aims to analyze the communication, interpersonal relationships and professional satisfaction of the nursing team. Cross-sectional, descriptive study carried out in five public hospitals of São Luís-MA from March 2011 to December 2015 with nursing professionals, totaling a population of 2270 professionals. The questionnaire for data collection was adapted from validated research instruments, containing the following variables: communication; Relationship with work; Commitment to the institution and job satisfaction. The data were tabulated in Microsoft Excel and the relative and absolute frequency analysis in the SPSS version 22 program. The research was approved by the Ethics and Research Committee of the Federal University of Maranhão with the opinion nº 23115-005865 / 2010-40, observing the Recommendations of Resolution 466/12. The sample comprised 1065 nursing professionals, the results show the majority of females (88.2%), aged between 31 and 40 years (32.2%) and mean of 39.6 years; High school education (45.9%), full graduate (19.1%); Professional category are nursing technicians (65.2%) and nurses (24.3%). The majority of nursing professionals stated that they did not use written communication (67.4%) and did not hold formal work meetings (62%). Concerning interpersonal relationships, most of them feel recognized by the coordinator (79.4%), have a good relationship with the coordinator (89.8%), trust that other professionals help solve any problems (92.2%) and They think they receive conscious treatment (72.9%). Among professionals, attitudes of isolation occurred in 19.4% and received constant criticism (20.7%). Satisfaction at work is present in 95.2%, feeling of accomplishment with work (90.6%), consider that their work is worth (96.9%). Autonomy at work is reported by 63.8%, they think of leaving the institution, 39%. It was verified that the written communication is infrequent among the nursing teams, the relationship between nursing professionals presented favorable results, it is noteworthy the communication between the professionals and the coordinator with recognition of the professional potential, being satisfied and accomplished with the job. There have been cases of bullying and professionals who are thinking of leaving the institution. Recognizing that working conditions provide a more relaxed environment, valuing professionals with a positive impact on care, it is expected that this study will stimulate the discussion and improvement of working conditions of the nursing team.